Pengaruh Perbedaan Kepadatan Benih dan Pemberian AB Mix terhadap Produktivitas Green fodder Gabah Padi - Tera Fit Rayani; Annisa Hakim; Yuni Resti (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to compare the differences in seed density and the addition of AB mix as a source of nutrition on the productivity of unhulled rice green fodder. Green fodder was grown by hydroponic using fodder trays. The variables measured were biomass production, conversion of green fodder to seeds and plant height. The experimental design used was a 2 x 2 factorial design with treatment factors is the differences in seed density (150 g/container and 250 g/container) and nutrition (without AB mix immersion and AB mix immersion). The results showed that biomass production and green fodder conversion were significantly (p<0.05) affected by seed density. Total biomass and green fodder conversion increased with increasing seed density. Seed densities of up to 250 grams per container produce the highest biomass weight with high conversion of seeds to green fodder. Soaking seeds using AB mix had no effect on biomass weight, conversion, and plant height. However, immersion using AB mix produces plant heights that tend to be taller.